Dual resonating C-band with enhanced bandwidth and broad X-band metamaterial absorber - Agarwal M.; Behera A.K.; Meshram M.K. (My University, 2025)
An absorber structure is proposed in this paper that has dual resonance in the C-band and shows broadband absorption characteristics in the X-band on altering its design parameters. The unit cell of the proposed absorber consists of closed-ring resonator with a metallic patch inside it, and the two are diagonally connected by a metallic arm. The unit cell of the proposed absorber fits in a volume of 6 × 6 × 1.6 mm3. The C-band absorber is having peak absorptivities of 95.7, 99, and 98.9 % at 4.69, 5.19, and 7.15 GHz, respectively. The two lower resonances are overlapped and provide the wide full width at half maximum (FWHM) bandwidth of 1.08 GHz. Another obtained band in the C-band region is having FWHM of 1.05 GHz. For X-band absorber, the peak absorptivity of 99.81 and 99.77 % is obtained at 8.94 and 10.68 GHz, and broad FWHM absorption bandwidth of 3.69 GHz is achieved. The simulated results are verified with the experimental results and found in close agreement. The proposed absorber shows identical absorption characteristics for TE- and TM-polarized wave and working well up to an incident angle of 45°. The power losses in the dielectric and at the resonator surface are also presented in the paper. © 2016, Springer-Verlag Berlin Heidelberg.